Untold stories of unfree labor: Asians in the Americas - Aisha Khan (NWIG, 1996)
[First paragraph]
The Cuba Commission Report: A Hidden History of the Chinese in Cuba. The Original English-Language Text of 1876 (Introduction by Denise Helly). Baltimore: Johns Hopkins University Press, 1993. viii + 160 pp. (Paper US$21.95)
Indentured Labor, Caribbean Sugar: Chinese and Indian Migrants to the British West Indies, 1838-1918. WALTON LOOK LAI. Baltimore: Johns Hopkins University Press, 1993. xxviii + 370 pp. (Cloth US$ 39.95)

The world system formed by European mercantile and industrial capitalism and the history of transcontinental labor migrations from Africa to the Americas have been amply documented. The genesis, evolution, and demise of New World slavery are subjects much scrutinized and debated, particularly since the 1960s. Enjoying a less extensive tradition of historiography are the variously devised alternative labor schemes that came on the heels of emancipation: the colonially-orchestrated efforts to contract free and voluntary workers to take the place of slaves in a system of production theoretically the moral antithesis of that earlier "peculiar institution." Yet scholarship on indentured labor systems has consistently revealed that the "freedom" of immigrant workers was merely nominal, the "voluntary" nature of their commitments arguable, and the indenture projects often only ideally a kinder, gentier form of labor extraction.